Common stress factors faced by elderly in Deoli area of Wardha district - Kumar, Bijyendra Sourabh; Nayak, Smrutiranjan; Dhande, Nikhil; Mudey, Abhay; Kumari, Lovely; Wagh, Vasant (International Journal of Medical Research and Review, 2016)
Background: Previous studies have shown that elderly people faced numerous socio-psychological problems like stress, declining authority, lack of respect in the family, loneliness, difference of opinion with family members. To study this we further conducted a study in the deoli area of Wardha district from June to August, 2015. Objective: To find out common stress factors faced by elderly of Deoli area in Wardha district. Methods: Observational cross-sectional study. Simple random sampling technique was followed to include the study unit in the study sample and the study unit was selected by using lottery method from among the elderly population in the deoli area. Result: Elderly are more stressed from psychosocial problems than physical problems. They mostly suffer from limitation of physical activity (78%), back pain (66%) and joint pain (54%), sleep disturbance (88%), decrease in social life (88%), poor concentration (76%), and financial dependency(50%). Conclusion: It is concluded that there is urgent need for efforts on the part of the government and non-government organization to ensure guaranteed income, health care, social services, recreation and other requirements of the aged which will go a long way to reduce the problems of elderly.